ANALISIS NILAI-NILAI PENDIDIKAN DALAM NOVEL NONA TEH DAN TUAN KOPI (PARAK) KARYA CROWDSTROIA - Irma Nur Maulidatur Rofikoh; Masykuri Bakri; Fita Mustafida (VICRATINA, 2019)
Education is a important element in the progress of a country, one of the influential educational figures in Indonesia is Ki Hajar Dewantara, who is famous for his teachings, ing ngarsa sung tulada (in front of giving an example), ing madya mangun karsa (in creating opportunities) tut wuri handayani (behind giving encouragement), for initiate. Therefore, these three concepts need to be grounded as the main pillars in the practice of education in Indonesia. In order for Indonesian people to grow into a person who is responsible, dynamic, innovative, faithful to the truth, has expertise (skills), and contributes to social development. Thus, the formation of the pancasila human character is also achieved. Education can be obtained not only through school, but also through literature, readers can reap the value contained in it, including the value of education. Based on this context the researcher focuses on the value of education contained in a literary work, in this case the novel. Keyword : Educational value, Novel